Analysis and Suggestions for Improvement of Marubeni Engine Performance at Pt. Indonesian Nuclear Industry (Persero) with Overall Equipment Effectiveness (OEE) Approach - Aris Munandar (International Journal of Mechanical Computational and Manufacturing Research, 2021)
The occurrence of downtime can cause the production process to stop and cause the resulting product to not match the specified quality. Therefore, downtime prevention must be carried out by conducting research to determine the effectiveness of the machine using the approach used in increasing the effectiveness of the machine is Total Productive Maintenance (TPM). Meanwhile, OEE (Overall Equipment Effectiveness) is a method used as a measurement in implementing the TPM program, in order to keep the equipment in ideal conditions by analyzing the Six Big Losses of the equipment. Based on the results of the calculation of the Rate of Quality of 72.92%, the value of the rate of quality product is still below the JIPM standard, namely 99%, because the quality level is not close to the standard number, which means that the number of reject products must be suppressed again, supported by the results. which is obtained from the Deffect Losses value of 24.01% and the Yield Losses value of 1.92. In order to obtain representative information for maintenance and continuous improvement (continuous improvement) in an effort to increase the effectiveness of machine use